Link between Industry 4.0 and green supply chain management: evidence from the automotive industry - Ghadge, Abhijeet; Mogale, Dnyaneshwar G.; Bourlakis, Michael; Maiyar, Lohithaksha Maniraj; Moradlou, Hamid (Elsevier, 2022)
The paper evidence the link between two paradigms - Industry 4.0 and Green Supply Chain Management (GSCM) following an empirical study conducted in the automotive industry. 243 responses from the automotive supply chain professionals from Europe (including the UK) are used to test the developed hypotheses. An integrated, two-stage approach combining interpretive structural modelling and structural equation modelling develops a multi-level hierarchical structure for establishing the link between Industry 4.0 technologies, Green Supply Chain (GSC) practices and GSC performance. The study evidenced an indirect effect of Industry 4.0 technologies through GSC practices on GSC performance; and this link is found to be stronger than the direct effect of Industry 4.0 and GSC practices in the automotive supply chains. Future supply chains should focus on driving and linking technologies such as the Internet of Things (IoT), Cyber-Physical Systems (CPS) and Blockchain for effective implementation of GSC practices. GSC practices, mainly reverse logistics and green purchasing, are highly influenced by disruptive technologies and are critical for leading improvement in GSC performance. Identifying and linking key Industry 4.0 technologies with GSC practices will benefit organizations in making evidence-informed decisions for improved sustainability performance.
Keywords: Industry 4.0; Internet of Things; Blockchain; Cyber-Physical Systems; Green supply chain management; Green practices; Sustainability; Automotive industry